Effects of Consumption Brew Robusta Coffee on Alveolar Bone Resorption in Rats Induced Periodontitis by Porphyromonas gingivalis - Ghafran Nailul Farchi; Rendra Chriestedy Prasetya; Nadie Fatimatuzzahro (Health Dynamics, 2024)
Background: Porphyromonas gingivalis is the main cause of periodontitis. The presence of virulence factors of this bacteria increases pro-inflammatory cytokines that can interfere with the remodeling of alveolar bones that will later occur alveolar bone resorption. Robusta coffee is a natural ingredient that contains various substances that are useful for inhibiting inflammation, such as chlorogenic acid, caffeic acid, and caffeine. The purpose of this study was to analyze the effect of steeped Robusta coffee consumption on alveolar bone in rats induced by Porphyromonas gingivalis. Methods: Twenty male Wistar rats divided into 5 groups, control group (K1), rats treated with P. gingivalis induction and was sacrificed on the 14th day (K2), rats treated with P. gingivalis induction with 3.6 ml of brew coffee and was sacrificed on the 14th day (K3), rats treated with P. gingivalis induction and sacrificed on the 28th day (K4), rats treated with P. gingivalis induction with 3.6 ml of brew coffee and sacrificed on the 28th day. The specimens were then processed histologically and stained with HE to determine alveolar bone resorption. Results: There was no significant difference between the induction P. gingivalis and the consumption of robusta brew coffee for 14 days with control group. It means that treated brew robusta coffee for 14 days had alveolar bone resorption similar with the control group. The induction group P. gingivalis with consumption of Robusta coffee brew for 28 days there was a significant difference with the control group. The induction group P. gingivalis with consumption of Robusta coffee brew for 14 days differed significantly from the treatment for 28 days, this could be due to the longer treatment resulting in more bacterial tissue exposure. Conclusion: Consumption of brew robusta coffee can inhibit the resorption of alveolar bone caused by Porphyromonas gingivalis.